Answer :


Given equation is,


4t-3-(3t + 1) = 5t-4


4t-3-3t-1 = 5t-4


t-4 = 5t-4


t-5t = -4 + 4 (transposing 5t to LHS and – 4 to RHS)


-4t = 0



Hence value of t is 0.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRD Sharma - Mathematics